KAJIAN TEORI MATEMATIKA EVERYONE IS A TEACHER HERE DAN PENDEKATAN QUANTUM TEACHING - Muntuan, Jade Rehulina (Jurnal Padegogik, 2018)
Mathematics is one of the subjects which is learned at all levels of education. Ithappens because mathematics is used and needed in every aspect human activity. One of theabilities students must possess is the ability to solve problems. Facts in Indonesia show thatstudents' mathematical problem-solving abilities at both secondary and tertiary educationlevels are still not high. From previous studies reported that only 35% of students had problemsolvingskills, 25% of students were able to design completion plans and 20% of students hadthe ability to solve problems. The remaining 20% are students who have the ability to lookback at the completion steps. Looking at the research reports above, the teachers are expectedto choose the right strategy to be used in carrying out the learning process in the classroom sothat the goals that have been written in the teaching plan can be achieved. A learning modelcalled "Everyone is a Teacher Here (ETH)" is an alternative learning to improve students'mathematical problem solving abilities. The ETH Learning Model provides opportunities forall students to act as "instructors" to their peers or in other words "peer tutors". Anotheralternative learning that can be used to improve students' mathematical problem solving skillsis the Quantum Teaching learning approach. The Quantum Teaching Approach can givestudents an active learning that stimulates the student's brain so that learning can runoptimally. This Quantum Teaching Approach has an activity framework in the form of Grow,Experience, Name, Demonstrate, Repeat, and Celebrate.